Complete mitochondrial genome of the Acentrogobius pflaumii (Gobiiformes, Gobiidae) with phylogenetic consideration - Hao Wu; Meiya Yu; Lei Zhou (Mitochondrial DNA. Part B. Resources, 2020)
The complete mitochondrial genome sequence of Acentrogobius pflaumii was sequenced. It was 16,515-nucleotide in length and consisted of 13 protein-coding genes, 2 ribosomal RNA genes, 22 transfer RNA genes, and two non-coding regions (L-strand replication origin and control region), showing conserved gene arrangement with most vertebrates. The phylogenetic analysis based on complete mitochondrial genome of A. pflaumii as well as other Gobiiformes species showed that A. pflaumii had close relationships with Amoya chusanensis. This study will provide useful genetic informatin for future phylogenetic and taxonomic classification of gobiiformes.